The Carter Administration's Attempt To Reconvene The Geneva Middle East Peace Conference - Guo Song (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
When the Carter administration assumed power in 1977, it prioritized the achievement of Middle East peace as its foremost task. It endeavored to facilitate a comprehensive Arab-Israeli peace by reconvening the Geneva Middle East Peace Conference and inviting representatives from Israel, Egypt, Syria, Jordan, and Palestine to negotiate a resolution to the Arab-Israeli conflict in Geneva. However, the Carter administration encountered challenges in its Arab-Israeli diplomacy, particularly regarding substantive and procedural issues related to restarting the conference. It struggled to reconcile differences between the Arab and Israeli sides on crucial peace-related matters such as borders and the inclusion of Palestinian delegates. Additionally, it faced difficulties in assisting Arab countries in resolving internal contradictions regarding their participation format. Ultimately, the Carter administration’s efforts to reconvene the Geneva Peace Conference fell short. This failure was attributed to several factors, including the deep-seated psychological divide between Arabs and Israelis, internal contradictions among Arab nations, the significant influence of pro-Israel forces in the United States constraining pressure on Israel, and President Carter’s limited experience in international affairs, coupled with underestimations of the complexities inherent in the Arab-Israeli conflict.
Keywords: The Palestinian representation